Monitoramento de afundamentos momentâneos de tensão e classificação por tipo, duração e magnitude - Patricia de Souza Carletto (2017)
The momentary voltage sags, despite being a short-lived phenomenon, is one of the most usual problems of the degradation of Electrical Energy Quality in the industrial sector. It can cause interruption of the productive flow, generating losses of the items in the manufacturing process, as it rejects and delays it. Sags are characterized with a reduction in voltage values (rms) for values between 0.1 to 0.9 pu (residual voltage), lasting between 1 cycle and 3 minutes. Considering that the sags occur in an industrial environment, many types of loads are sensitive to them. The single-phase type, two-phase or three-phase sags, as well as their magnitude and duration determine the loads susceptibility. Besides that, it is also necessary to know the occurrence profile of the events to define the most appropriate mitigation solution for these sags. This works presents the results of 16 months monitoring analysis at the Tesla Laboratory of the UFMG, in order to know the characterizing of the sags, in the period from September/2015 to December/2016